Luminescent mononuclear Eu(III) and Tb(III) complexes with bipyridyl-tetrazolate tridentate ligands. (15th October 2016) - Chen, Jing-Lin; Luo, Yan-Sheng; Gao, Guo-Ping; Zhao, Jia-Li; Qiu, Lu; Liu, Na; He, Li-Hua; Liu, Sui-Jun; Wen, He-Rui
Graphical abstract: The structural features and luminescence properties of Ln(III) complexes can be well modulated by the introduction of two methyl groups into the 2, 2′-bipyridyl ring. Abstract: A new series of four luminescent mononuclear Eu(III) and Tb(III) complexes with bipyridyl tetrazolate tridentate chelates, [Ln(tbpy)2 (DMF)(H2 O)2 ](NO3 ) and [Ln(tmbpy)2 (DMF)(NO3 )] (Ln = Eu(III) and Tb(III), DMF = N, N-dimethylformamide, tbpy and tmbpy denote the deprotonated 6-(1 H -tetrazole-5-yl)-2, 2′-bipyridine and 6-(1 H -tetrazole-5-yl)-4, 4′-dimethyl-2, 2′-bipyridine, respectively), have been synthesized and characterized. Each Ln(III) ion displays a distorted tricapped trigonal prism with two mono-anionic tridentate chelating ligands, originating from the N–H deprotonation of the tetrazolyl ring, and the introduction of two methyl groups into the 2, 2′-bipyridyl ring has a significant impact on the coordination environment of the Ln(III) core, exhibiting that two coordinated water molecules are displaced by one chelating nitrate anion. Two types of Ln(III) complexes are all emissive in solution and solid states at room temperature. It is shown that the introduction of two electron-donating methyl groups into the 2, 2′-bipyridyl ring has a major effect on the photoluminescence of Ln(III) complexes, and it is favorable for improving the luminescence efficiencies of Ln(III) species.